2002
DOI: 10.1172/jci0215693
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of leptin on obesity, T cell hyporesponsiveness, and neuroendocrine/metabolic dysfunction of human congenital leptin deficiency

Abstract: The wide range of phenotypic abnormalities seen in the leptin-deficient ob/ob mouse and their reversibility by leptin administration provide compelling evidence for the existence of multiple physiological functions of this hormone in rodents. In contrast, information regarding the roles of this hormone in humans is limited. Three morbidly obese children, who were congenitally deficient in leptin, were treated with daily subcutaneous injections of recombinant human leptin for up to 4 years with sustained, benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
699
4
58

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,159 publications
(777 citation statements)
references
References 41 publications
16
699
4
58
Order By: Relevance
“…Strikingly, we have shown that the principal impact of leptin on these children is a marked reduction in spontaneous food intake. 30,31 Thus, we were able to complete the 'Koch's postulates' for leptin as an appetite regulatory hormone in humans and confirmed that human appetite and food intake, similar to the mouse, are dependent on the presence of an active leptin signaling pathway. In subsequent years, we and others have shown that human obesity can result from a multiplicity of defects in the downstream pathways of leptin signaling within the brain.…”
Section: Discussionsupporting
confidence: 59%
“…Strikingly, we have shown that the principal impact of leptin on these children is a marked reduction in spontaneous food intake. 30,31 Thus, we were able to complete the 'Koch's postulates' for leptin as an appetite regulatory hormone in humans and confirmed that human appetite and food intake, similar to the mouse, are dependent on the presence of an active leptin signaling pathway. In subsequent years, we and others have shown that human obesity can result from a multiplicity of defects in the downstream pathways of leptin signaling within the brain.…”
Section: Discussionsupporting
confidence: 59%
“…In studies of the effects of leptin administration on TSH, findings differed depending on whether basal TSH concentrations or TSH secretion were examined. For example, administration of leptin to leptindeficient children 47 and healthy adults 48 increases thyroid hormones without altering basal TSH concentration. In contrast, leptin replacement significantly blunts the 24-hour TSH (µU/ml) 24-hour leptin (ng/ml) Figure 3 Linear relationship between mean 24-h levels of leptin and TSH in 16 morbidly obese subjects basally (open circles), in 7 morbidly obese subjects after 6 months of surgery (filled circles) and in lean control subjects (filled triangles).…”
Section: Discussionmentioning
confidence: 99%
“…55,92 FUTURE PROSPECTS Exogenous leptin administration in children with a congenital leptin deficiency normalized the absolute numbers of Tregs, enhanced CD4 1 counts, restored proliferative responses, and promoted the cytokine release profile from lymphocytes. 15 Furthermore, it has been demonstrated that the exogenous administration of recombinant methionyl human leptin in subjects with acquired leptin deficiency improves their circulating cytokine levels. 44 However, there is a huge amount of data on the promotion of inflammation by high circulating leptin levels.…”
Section: Leptin Connective Tissue Diseases and Organ-specific Autoimmentioning
confidence: 99%